Income distribution inequality and its implications for regional economic growth - Marshanda; Kinanti (Economy, Business, Finance, Accounting & Management Journal, 2025)
Income distribution inequality remains a critical challenge in achieving sustainable and inclusive economic growth. This study examines the relationship between income inequality and regional economic growth, with a focus on identifying the mechanisms through which unequal distribution of income influences long-term development trajectories. Using panel data from multiple regions over a ten-year period, the research employs the Gini coefficient as a measure of inequality and real GDP growth rates as an indicator of economic performance. Econometric analysis is conducted using fixed-effects and generalized method of moments (GMM) estimations to address potential endogeneity issues. The findings reveal a non-linear relationship, where moderate inequality may initially stimulate investment and growth by concentrating capital among high-saving households, but excessive inequality tends to hinder growth through reduced aggregate demand, limited human capital development, and social instability. The study also finds that regions with better access to education, healthcare, and infrastructure exhibit greater resilience to the negative effects of inequality. Policy implications suggest that promoting equitable access to economic opportunities particularly through targeted fiscal policies, progressive taxation, and investment in social infrastructure can mitigate inequality without discouraging productivity and innovation. This research contributes to the ongoing discourse on inclusive growth strategies and underscores the need for region-specific approaches in addressing income disparities to foster balanced and sustainable economic development